RESTORE ME: a RCT of oxaloacetate for improving fatigue in patients with myalgic encephalomyelitis/chronic fatigue syndrome - Cash, Alan; Vernon, Suzanne D.; Rond, Candace; Bateman, Lucinda; Abbaszadeh, Saeed; Bell, Jennifer; Yellman, Brayden; Kaufman, David L. (Frontiers in Neurology, 2024)
The energy metabolite oxaloacetate is significantly lower in the blood plasma of ME/CFS subjects. A previous open-label trial with oxaloacetate supplementation significantly reduced ME/CFS fatigue.In a follow-on trial, 82 ME/CFS subjects were enrolled in a 3-month randomized double blinded controlled trial using 2,000 mg oxaloacetate or control/day. The primary endpoints were safety and a reduction in fatigue from baseline. Secondary and exploratory endpoints reviewed functional capacity, and general health status.Results: Anhydrous enol-oxaloacetate (oxaloacetate) was well tolerated at the doses tested. Oxaloacetate significantly lowered fatigue from baseline by >25%, whereas the control group was not significant at ~10% reduction. Intergroup analysis of oxaloacetate and control measured shifted fatigue to lower levels in the oxaloacetate group (P= 0.0039), but with no significant shift in the control group. The oxaloacetate group had a higher percentage of subjects achieve a > 25% reduction in fatigue compared to the control group (P< 0.05). A subset of subjects that comprised 40.5% of the oxaloacetate group were "Enhanced Responders" with a 63% average fatigue reduction. Both physical and mental fatigue were improved by oxaloacetate.Oxaloacetate is well-tolerated and helps to reduce fatigue in ME/CFS.